RECONSTRUCTING MOBILE BRIGADE AUTHORITY IN LAW ENFORCEMENT OPERATIONS WITHIN ARMED CRIMINAL GROUP CONFLICT AREAS BASED ON LEGALITY AND HUMAN RIGHTS - Amir Hasan A; Yusuf Daeng; Rudi Pardede (JILPR Journal Indonesia Law and Policy Review, 2026)
The purpose of this study is to analyze the reconstruction of the authority of the Indonesian National Police Mobile Brigade in law enforcement operations in conflict-prone areas affected by armed criminal groups based on the principles of legality and human rights. The authority and assignment mechanisms of the Indonesian National Police Mobile Brigade Corps in efforts to restore regional security against armed criminal groups in conflict areas are analyzed. The method used is normative legal research. Based on the research results, it is known that the reconstruction of the authority of the Indonesian National Police Mobile Brigade in law enforcement operations in areas prone to armed criminal group conflicts based on the principles of legality and human rights is basically derived from the attribution authority granted by Law Number 2 of 2002 concerning the Indonesian National Police, specifically Article 13 and Article 14 which regulate the task of maintaining public security and order and law enforcement. However, these regulations are still general in nature and have not specifically regulated the authority of Brimob in dealing with armed criminal groups that have the characteristics of high-intensity threats, use modern weaponry, and apply guerrilla patterns that resemble non-international armed conflicts. This research found a legal vacuum and normative inconsistency that specifically regulates the definition of armed criminal groups, threat classification, limits of Brimob's authority, mechanisms for TNI involvement, operational command structures, standards for the use of force, and mechanisms for protecting human rights in security operations in conflict areas. Therefore, the reconstruction of Brimob's authority must be carried out through the creation of special regulations that place Brimob as the leading sector in law enforcement operations, clarify the TNI assistance mechanism, strengthen the principle of legality, and integrate human rights protection standards based on the principles of legality, necessity, proportionality, and accountability.